A nanosecond pulse-compression microwave radar; Telecommunications and Radio Engineering; Vol. 54, № 2 - Yushkov Y. G. Yuri Georgievich (2000, 2000)
Some characteristic features of high-power ultra-short microwave pulses produced by accumulating and rapid extraction of electromagnetic energy from cavities are examined. Results of the first experimental investigations of a breadboard nanosecond radar are presented